DIAGNOSING POVERTY ERADICATION THROUGH LITERACY: ANALYSIS FROM NATIONAL SOCIOECONOMIC SURVEY NORTH SUMATERA PROVINCE - Budi Rusdianto; Nuri Rahayu; Timoria Sitorus; Rusiadi; Suhendi (ZILLZELL MEDIA PRIMA, 2024)
This study supposed to determine the factors that influence the poverty rate in North Sumatra Province. This study used cross sectional data from the North Sumatra Province Socio-Economic Survey 2023. This survey is a survey conducted by the Central Bureau of Statistics (BPS), which aims to collect data on the socio-economic conditions of the community related to the fields of education, health/nutrition, housing, socio-cultural activities, consumption/expenditure and household income, travel, and opinions on household welfare. household. The Socio-Economic Survey of North Sumatra Province 2023 survey data collected by BPS in March 2023 covered 33 regencies/cities in North Sumatra Province with 5000 sample households spread across 325 sub-districts and representing the entire population. The results of this study are literacy has a positive and significant effect on poverty in North Sumatra Province, financial literacy has a positive and significant effect on poverty in North Sumatra Province and age has a positive and significant effect on poverty in North Sumatra Province.